A layer-by-layer approach based on APTES/Cloisite to produce novel and sustainable high performances materials based on hemp fiberboards. (April 2022) - Viscusi, Gianluca; Liparoti, Sara; Pantani, Roberto; Barra, Giuseppina; Gorrasi, Giuliana
Highlights: A layer by layer approach was used to produce composites based on hemp fiberboards. The influence of the number of layers on physical properties was investigated. A decrease in burning rate were observed in samples treated with cloisite. A mechanism concerning the flame retardancy was proposed. Abstract: The paper presents a hybrid and smart methodology, using the layer-by-layer approach, to produce high performant multi-layered composites based on hemp fiberboards with improved physical properties. The effect of an inorganic component, such as a natural clay, and the surface covering with an organic compound, such as stearic acid, was investigated through the analysis of morphological, spectroscopic, thermal, mechanical and barrier properties of the composites. Vertical burning test confirmed the improvement in flame retardancy of layered composites since the presence of clay. The oil adsorption capacity was evaluated and correlated to the number of clay layers. Finally, a possible mechanism of combustion was proposed. Graphical abstract: Image, graphical abstract